2017
DOI: 10.3390/molecules22050763
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Essential Oil-Derived β-Methoxyacrylate Derivatives as High Potential Fungicides

Abstract: Essential oils (EOs) are plant-derived aroma compounds with a wide range of biological activity, but their actions are slow, and they are typically unstable to light or heat, difficult to extract and so on. To find highly potential fungicides derived from natural EOs, a series of essential oil-based β-methoxyacrylate derivatives have been designed and synthesized. The target compounds have been screened for their potential fungicidal activity against eleven species of plant pathogen fungi, including Alternaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Previous literature studies have shown that frying with bran can reduce the dryness of the drug and improve its spleen tonifying activity [49]. EOs are plant-derived aromatic compounds that have a wide range of biological activities, but they act slowly, and they are usually unstable under light or heat, difficult to extract, and so on [50]. Based on this, we used GC/MS to study the EOs components of CA and BA.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature studies have shown that frying with bran can reduce the dryness of the drug and improve its spleen tonifying activity [49]. EOs are plant-derived aromatic compounds that have a wide range of biological activities, but they act slowly, and they are usually unstable under light or heat, difficult to extract, and so on [50]. Based on this, we used GC/MS to study the EOs components of CA and BA.…”
Section: Discussionmentioning
confidence: 99%
“…Compound 70 , containing a pyrrolidine-2,4-dione moiety, exhibited moderate fungicidal activity against B. cinerea , R. solani , and Fusarium graminearum at 100 μg/mL, still better than that of tenuazonic acid . Compound 71 bearing a carbazole side chain displayed outstanding activity against S. sclerotiorum with IC 50 value of 0.43 μg/mL, close to that of pyraclostrobin (0.15 μg/mL) . Compound 72 possessing an aryloxypyridine as side chain exhibited remarkable activity against S. sclerotiorum with EC 50 value of 0.08 μg/mL, 10-fold more potent than that of azoxystrobin (EC 50 = 0.79 μg/mL) …”
Section: β-Methoxyacrylate Derivatives As Pesticidesmentioning
confidence: 98%
“…Field trials showed that the fungicidal activities of compound 30 were almost equivalent to those of pyraclostrobin, higher than those of triadimefon . The essential oil-based strobilurin 31 showed remarkable in vitro inhibitory activities against S. sclerotiorum , Pestalotiopsis theae , Magnaporthe grisea , and Phomopsis adianticola with EC 50 values of 0.003, 0.04, 0.95, and 3.06 μg/mL, respectively, which were superior to those of azoxystrobin (EC 50 = 18.75, 2.54, 2.41, and 35.3 mg/L, respectively) . Compound 32 , possessing a biphenyl group as side chain, displayed significant activities against B. cinerea with IC 50 value of 0.57 μg/mL, close to that of pyraclostrobin (IC 50 = 0.18 μg/mL).…”
Section: β-Methoxyacrylate Derivatives As Pesticidesmentioning
confidence: 99%
“…Essential oil-based β-methoxyacrylate derivatives have been synthesized and showed remarkable inhibitory activities against P. theae. 16 Major tea leaf volatile constituents, including geraniol, linalool, methyl salicylate, benzyl alcohol, and 2-phenylethanol, were found to exhibit significant antifungal activities toward Colletorichum camelliae Massea. 17 Marine environments, with a wide range of temperature, pressure, salt concentration, and pH, are known to be a rich resource for bioactive natural products.…”
Section: ■ Introductionmentioning
confidence: 98%
“…To date, there have only been a few reports on active compounds against tea pathogenic fungi. Essential oil-based β-methoxyacrylate derivatives have been synthesized and showed remarkable inhibitory activities against P. theae . Major tea leaf volatile constituents, including geraniol, linalool, methyl salicylate, benzyl alcohol, and 2-phenylethanol, were found to exhibit significant antifungal activities toward Colletorichum camelliae Massea .…”
Section: Introductionmentioning
confidence: 99%